Pengaruh Return on Asset, Return on Equity, dan Earning Per Share terhadap Harga Saham pada Perusahaan Tekstil dan Garmen yang Terdaftar di BEI - Grace Sriati Mengga (Journal on Education, 2023)
The purpose of this study was to determine the effect of Return on Assets, Return on Equity and Earning Per Share on Stock Prices in Textile and Garment Companies that are listed on the IDX. The type of research used is quantitative and the data collection technique is library research. The sample used is as many as 5 companies. The data analysis technique used is the multiple linear regression method. The analytical tool used is the SPSS application version 24. The results of this study indicate that the ROA variable has a positive and significant effect on the stock prices of Textile and Garment companies listed on the IDX, the ROE variable has a positive and insignificant effect on stock prices in Textile and Garment companies listed on the Stock Exchange. IDX and EPS variables that have a negative and insignificant effect on stock prices in Textile and Garment companies listed on the IDX.